Neural precursor cells in the ischemic brain – integration, cellular crosstalk, and consequences for stroke recovery - Hermann, Dirk M.; Peruzzotti-Jametti, Luca; Schlechter, Jana; Bernstock, Joshua D.; Doeppner, Thorsten R.; Pluchino, Stefano (Frontiers in Cellular Neuroscience, 2014)
After an ischemic stroke, neural precursor cells (NPCs) proliferate within major germinal niches of the brain. Endogenous NPCs subsequently migrate toward the ischemic lesion where they promote tissue remodeling and neural repair. Unfortunately, this restorative process is generally insufficient and thus unable to support a full recovery of lost neurological functions. Supported by solid experimental and preclinical data, the transplantation of exogenous NPCs has emerged as a potential tool for stroke treatment. Transplanted NPCs are thought to act mainly via trophic and immune modulatory effects, thereby complementing the restorative responses initially executed by the endogenous NPC population. Recent studies have attempted to elucidate how the therapeutic properties of transplanted NPCs vary depending on the route of transplantation. Systemic NPC delivery leads to potent immune modulatory actions, which prevent secondary neuronal degeneration, reduces glial scar formation, diminishes oxidative stress and stabilizes blood–brain barrier integrity. On the contrary, local stem cell delivery allows for the accumulation of large numbers of transplanted NPCs in the brain, thus achieving high levels of locally available tissue trophic factors, which may better induce a strong endogenous NPC proliferative response. Herein we describe the diverse capabilities of exogenous (systemically vs. locally transplanted) NPCs in enhancing the endogenous neurogenic response after stroke, and how the route of transplantation may affect migration, survival, bystander effects and integration of the cellular graft. It is the authors’ claim that understanding these aspects will be of pivotal importance in discerning how transplanted NPCs exert their therapeutic effects in stroke.